Kepemimpinan Islami Yayasan KH Djazeri Demak - Lilistigfaroh Rohmalia; Ahyar Yuniawan; Mirwan Surya Perdhana (Universitas Diponegoro, 2020)
This research is a case study of Islamic Leadership by K.H Ahmad Toha, informant K.H Ahmad Toha, his family, and employees of Yayasan K.H Djazeri. Data obtained using interviews, observation, and documentation, are then analyzed qualitatively.The results of the research is the application of Islamic Leadership by K.H Ahmad Toha is one manifestation of Islamic management system in Yayasan K.H Djazeri. This is due to the strong influence of religious values in the family. In addition, management perceptions of islam as a comprehensive management concept impeccable alse a factor affecting the implementation of islamic management system which ultimately affects the islamic leadership by K.H Ahmad Toha. Islamic Leadership by K.H Ahmad Toha have characteristics shiddiq, amanah, tabligh, fathonah.